Saturation of Global Terrestrial Carbon Sink Under a High Warming Scenario. Issue 10 (9th October 2021) - Shi, Hao; Tian, Hanqin; Pan, Naiqing; Reyer, Christopher P. O.; Ciais, Philippe; Chang, Jinfeng; Forrest, Matthew; Frieler, Katja; Fu, Bojie; Gädeke, Anne; Hickler, Thomas; Ito, Akihiko; et al.
Abstract: The terrestrial carbon sink provides a critical negative feedback to climate warming, yet large uncertainty exists on its long‐term dynamics. Here we combined terrestrial biosphere models (TBMs) and climate projections, together with climate‐specific land use change, to investigate both the trend and interannual variability (IAV) of the terrestrial carbon sink from 1986 to 2099 under two representative concentration pathways RCP2.6 and RCP6.0. The results reveal a saturation of the terrestrial carbon sink by the end of this century under RCP6.0 due to warming and declined CO2 effects. Compared to 1986–2005 (0.96 ± 0.44 Pg C yr −1 ), during 2080–2099 the terrestrial carbon sink would decrease to 0.60 ± 0.71 Pg C yr −1 but increase to 3.36 ± 0.77 Pg C yr −1, respectively, under RCP2.6 and RCP6.0. The carbon sink caused by CO2, land use change and climate change during 2080–2099 is −0.08 ± 0.11 Pg C yr −1, 0.44 ± 0.05 Pg C yr −1, and 0.24 ± 0.70 Pg C yr −1 under RCP2.6, and 4.61 ± 0.17 Pg C yr −1, 0.22 ± 0.07 Pg C yr −1, and ‐1.47 ± 0.72 Pg C yr −1 under RCP6.0. In addition, the carbon sink IAV shows stronger variance under RCP6.0 than RCP2.6. Under RCP2.6, temperature shows higher correlation with the carbon sink IAV than precipitation in most time, which however is the opposite under RCP6.0. These results suggest that the role of terrestrial carbon sink in curbing climate warming would be weakened in a no‐mitigation world in future, and active mitigation efforts are required as assumed under RCP2.6. Key Points: Elevated temperature has negative impacts on terrestrial carbon sink CO2 effects on terrestrial carbon sink saturate at high CO2 concentration Interannual variability of terrestrial carbon sink is more correlated with temperature under RCP2.6 but precipitation under RCP6.0